2015
DOI: 10.5194/hess-19-2409-2015
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective parameter optimization of common land model using adaptive surrogate modeling

Abstract: Abstract. Parameter specification usually has significant influence on the performance of land surface models (LSMs). However, estimating the parameters properly is a challenging task due to the following reasons: (1) LSMs usually have too many adjustable parameters (20 to 100 or even more), leading to the curse of dimensionality in the parameter input space; (2) LSMs usually have many output variables involving water/energy/carbon cycles, so that calibrating LSMs is actually a multi-objective optimization pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 57 publications
1
61
0
Order By: Relevance
“…This is supported by a number of other studies [Xia et al, 2002;Rosolem et al, 2013;Gong et al, 2015]. However parameter tuning at PFT level does not reduce model errors uniformly across all land points within a PFT, as found in this study.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2015mssupporting
confidence: 77%
“…This is supported by a number of other studies [Xia et al, 2002;Rosolem et al, 2013;Gong et al, 2015]. However parameter tuning at PFT level does not reduce model errors uniformly across all land points within a PFT, as found in this study.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2015mssupporting
confidence: 77%
“…Calibration of input parameters using observations and the simplified system is possible if the simulation setup matches observation locations. Recent research using CLM suggests that reduced-form models can be used to reduce the number of simulations required for parameter optimization (Gong et al, 2015), adjust parameter values used to predict methane emission from wetlands (Müller et al, 2015) and calibrate parameters identified as important for latent heat estimates (Ray et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other similar satisfactory optimization results were determined [54] by his research on hydrological parameter classifi cation. [54] has modeled in his studies on study [55][56][57][58], showing that the values of parameters on PCA diagrams can be presented as tables correlating between investigated parameters. At the same time, in order to identify the missing data and their uncertainties in complex computational models, a reliable approach to analysis is needed.…”
Section: Resultsmentioning
confidence: 99%